Comorbidity prevalence and healthcare costs in people living with HIV compared with the general population: a 19-year retrospective cohort study in British Columbia, Canada - Robert S Hogg; Silvia Guillemi; Viviane D Lima; Hasan Nathani; Carly Magee; Michael Budu; Morris Chan; Bronhilda Takeh; Katherine W Kooij; Julio G S Montaner (BMJ Open)
Objectives Our objectives were (1) to characterise the age-sex-standardised prevalence of comorbidities among people living with HIV (PLWH) and people not living with HIV (PnLWH) between 2001 and 2019 and (2) to examine the effect of comorbidities on direct healthcare costs among PLWH and PnLWH.Design This was a retrospective, matched cohort study conducted with the Comparative Outcomes and Service Utilisation Trends (COAST) cohort, which contained all known PLWH in British Columbia (BC), Canada and a general population sample.Setting BC, Canada.Participants A total of 9554 PLWH and 47 770 PnLWH from the COAST cohort were followed between 2001 and 2019. Participants were at least 19 years old and 82% male in both groups.Outcome measures The primary outcomes were the age-sex-standardised prevalence of 16 comorbidities, calculated annually, among PLWH and PnLWH. Secondary outcomes included direct healthcare costs associated with each comorbidity among PLWH and PnLWH. Outcomes were ascertained from administrative health databases.Results PLWH exhibited a higher age-sex-standardised prevalence of most comorbidities compared with PnLWH over the study period. Relative disparities in liver and kidney diseases markedly decreased since 2008. Disparities in the prevalence of mental health disorders and substance use disorder (SUD) were consistently large throughout the study period. Comorbidities were associated with high healthcare costs, especially among PLWH.Conclusions This study underscores the persistent and evolving burden of non-AIDS-defining comorbidities among PLWH, even in the context of improved HIV management. The high prevalence of mental health disorders and SUD, coupled with the substantial healthcare costs associated with these conditions, emphasises the need for holistic and integrated care models that address the full spectrum of health challenges faced by PLWH.